2014
DOI: 10.1007/s13595-014-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing deer browsing pressure influenced understory vegetation dynamics over 30 years

Abstract: Abstract& Key message Thanks to the concomitant recordings of vegetation and deer browsing sampled first in 1976, then resurveyed in 2006, we show that forest plant communities shifted in response to deer population dynamics, stand management and eutrophication. & Context and aims High deer populations alter forest understory dynamics worldwide. However, no study ever attempted to rank the importance of deer herbivory relatively to other environmental drivers. In the Arc-en-Barrois National Forest (France), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
4
23
0
2
Order By: Relevance
“…They hypothesized that the long range gradients could be explained by atmospheric nitrogen deposition deeper inside forest interior, in accordance with previous investigations that detected DEI over 500 m into forest interior for MIV N (Thimonier et al, 1992;Kennedy & Pitman, 2004). Other ecological processes are linked to ungulate movements between forest habitats and crops for feeding across forest edges (Bleier et al, 2012) and their role in seed dispersal (endo-and epi-zoochory, Albert et al, 2015) and browsing pressure (Boulanger et al, 2015) in temperate landscapes.…”
Section: Plant Response To Environmental Processes Related To Presentsupporting
confidence: 81%
See 1 more Smart Citation
“…They hypothesized that the long range gradients could be explained by atmospheric nitrogen deposition deeper inside forest interior, in accordance with previous investigations that detected DEI over 500 m into forest interior for MIV N (Thimonier et al, 1992;Kennedy & Pitman, 2004). Other ecological processes are linked to ungulate movements between forest habitats and crops for feeding across forest edges (Bleier et al, 2012) and their role in seed dispersal (endo-and epi-zoochory, Albert et al, 2015) and browsing pressure (Boulanger et al, 2015) in temperate landscapes.…”
Section: Plant Response To Environmental Processes Related To Presentsupporting
confidence: 81%
“…Peripheral species were much more nitrogen-demanding, had higher pH indicator values and were more urbanophilic than core species. Other ecological processes are linked to ungulate movements between forest habitats and crops for feeding across forest edges (Bleier et al, 2012) and their role in seed dispersal (endo-and epi-zoochory, Albert et al, 2015) and browsing pressure (Boulanger et al, 2015) in temperate landscapes. However, we detected periphery-to-core gradients with much longer DEI than previously recognized, which suggests underlying processes other than the usual short range edge effect, such as atmospheric deposition, browsing pressure or seed pressure.…”
Section: Plant Response To Environmental Processes Related To Presentmentioning
confidence: 99%
“…This feeding behaviour is due mainly to high adaptability of wild animals to utilise also species considered of reduced quality, and in this way selectivity can be considered one of the most important factors affecting animal preferences (Rook et al, 2004). Wild animals in our trial showed performances similar to what described by Orth et al (1998), by Moser et al (2008) or by Freschi et al (2014), concerning variability of animal utilisation according to seasonal changes in food resources availability, or by Boulanger et al (2015) that reported high browsing activity performed by wild ungulates on species of no quality or even toxic. Concerning level of utilisation, data of percentage of browsing is consistent with those of Ponzetta et al (2010) and Iussig et al (2015).…”
Section: Articlesupporting
confidence: 81%
“…Correspondence among browsing data found through botanical analysis and camera traps is represented by the existence of a significant regression between total browsing scores and number of videos recorded in each plots belonging to different species and mixtures ( Figure 5). In this way both methods proved to be interesting for future assessment of utilisation activity of wild animals, especially ungulates (Kuijper et al, 2009), and they could be useful tools for territorial management purposes and to examine evolution of plant communities under the determinant driver represented by wild animals population dynamic (Boulanger et al, 2015).…”
Section: Articlementioning
confidence: 99%
“…Increasing ungulate populations are an issue for forest managers since the damages they may cause to trees and seedlings can jeopardize forest regeneration processes (Bradshaw & Waller, 2016). Many studies have been carried out under high densities of ungulate populations (Habeck & Schultz, 2015) obtained either experimentally (Bachand et al, 2014) or naturally (Martin, Stockton, Allombert, & Gaston, 2010), or resulting from local management choices (Baltzinger et al, 2016), or in areas where noticeable impacts had been a priori observed (Boulanger et al, 2015). The roles of ungulates as general drivers of changes in forest dynamics and biodiversity have been less investigated in standard conditions.…”
Section: Introductionmentioning
confidence: 99%